THE SUCCESS ANALYSIS OF IMPLEMENTATION OF THE ELECTRONIC SYSTEM INTEGRATED FINAL PROJECT OF JAMBI UNIVERSITY STUDENTS WITH DELONE AND MCLEAN MODEL APPROACH - WIRMIE EKA PUTRA; DEDY SETIAWAN (JEBI (Jurnal Ekonomi dan Bisnis Islam), 2019)
The purpose of this research was able to prove empirically about the Delone and Mclean Models for the evaluation of ELISTA information systems at Jambi University. In addition, this research was also expected to provide feedback to improve the efficiency and effectiveness of the implementation of information systems and can be known the factors that cause the success or failure of the implementation of an information system so that the results of this study can be used as a strategic guideline model for information system development in the university and other institutions. The type of data used in this study was primary data obtained directly from respondents using a list of statements in the form of a questionnaire. Final year students who write the thesis are targeted in this study. To calculate the determination of the number of samples, the sampling method used the Hair method. The total sample of this study was 220 people. Methodology Data analysis was carried out using SEM techniques using SmartPLS tools. The findings in this study found that the system quality does not affect the user satisfaction, while other hypotheses such as information quality, service quality, system use affect user satisfaction, for system quality, information quality, and service quality affect the system use. Likewise the system use affects user satisfaction and system use, user satisfaction has an influence on net benefits.